2017
DOI: 10.12911/22998993/76834
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Land Amelioration Systems in the Catchment of the Rów Wyskoc River in the Context of their Use to Counteract the Effects of Drought

Abstract: The regulation of water relations is an important environmental role of permanent greeneries . The valleys used as permanent grasslands often also function as polders or dry flood-control reservoirs. The land amelioration systems realized in the 1970s and 1980s, for economic reasons do not perform the functions they were planned to. Tjis is because their exploitation has been abandoned and the systems still drain the land in an uncontrolled way, i.e.. without the regulation of water level assumed in the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, by 2023, only 100 wetlands remained. This was primarily the result of large-scale land reclamation efforts initiated in the late 1960s and carried out during the 1970s to the early 1980s 62 , 64 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, by 2023, only 100 wetlands remained. This was primarily the result of large-scale land reclamation efforts initiated in the late 1960s and carried out during the 1970s to the early 1980s 62 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…They also had the flood protection function. Research by Kozaczyk 62 examined the water regulation impact on the permanent grasslands and their exploitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists emphasize that in Poland, the problem is too little funding and not enough emphasis on the maintenance work of the structures, which results in the deterioration of the condition and functionality of drainage facilities on many meadow sites [21,22]. Moreover, based on archival maps, it was also found that the irrigation system in Racot village in 1976 consisted of as many as 36 km of ditches, whereas in 2000, it was only 12.5 km [23].…”
Section: Research Area and Experiments Designmentioning
confidence: 99%